Characterisation of Phenolic Compounds by HPLC–TOF/IT/MS in Buds and Open Flowers of 'Chemlali' Olive Cultivar. Issue 5 (28th June 2013) - Taamalli, Amani; Abaza, Leila; Arráez Román, David; Segura Carretero, Antonio; Fernández Gutiérrez, Alberto; Zarrouk, Mokhtar; Ben Youssef, Nabil; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction Plant phenolics are secondary metabolites that constitute one of the most widely occurring groups of phytochemicals that play several important functions in plants. In olive (Olea europaea L), there is not enough information about the occurrence of these compounds in buds and flowers. Objective To conduct a comprehensive characterisation of buds and open flowers from the olive cultivar 'Chemlali'. Methods The polar fraction of buds and open flowers was extracted using solid–liquid extraction with hydro‐alcoholic solvent. Then extracts were analysed using high performance liquid chromatography (HPLC) coupled to electrospray ionisation time‐of‐flight mass spectrometry (ESI/TOF/MS) and electrospray ionisation ion‐trap tandem mass spectrometry (ESI/IT/MS2) operating in negative ion mode. Results Phenolic compounds from different classes including secoiridoids, flavonoids, simple phenols, cinnamic acid derivatives and lignans were tentatively identified in both extracts. Qualitatively, no significant difference was observed between flower buds and open flowers extracts. However, quantitatively the secoiridoids presented higher percentage of total phenols in open flowers (41.7%) than in flower buds (30.5%) in contrast to flavonoids, which decreased slightly from 38.1 to 26.7%. Cinnamic acid derivatives and simple phenols did not show any change. Lignans presented the lowest percentage in both extracts with an increase during the development of the flower bud to open flower. Conclusion The HPLC–TOF/IT/MS allowed the characterisation, for the first time, of the phenolic profile of extracts of 'Chemlali' olive buds and open flowers, proving to be a very useful technique for the characterisation and structure elucidation of phenolic compounds. Copyright © 2013 John Wiley & Sons, Ltd.